Model Pembelajaran Kewirausahaan Di Perguruan Tinggi (Studi Kasus Di STIEBBANK Yogyakarta) - Joko Indro Cahyono; Samsi Haryanto (EBBANK, 2014)
This study aimed to the preparation of the SAP (Unit Event Class) Entrepreneurship, application of learning models, the results achieved from the application of learning, and the obstacles encountered in teaching entrepreneurship. The study population 155 students STIEBBANK Yogyakarta in 2013/2014 consisting of Management Studies and Accounting. Samples were taken 70 questionnaire respondents. Data collection was conducted by questionnaire in addition, also in-depth interview with the Chairman and Vice Chairman for Academic Affairs, faculty, students, and alumni. Also obtained from observations in the field, and is supported by documents. Analysis techniques to test the validity of the data is triangulated.The results showed that the preparation of the SAP EP (Entrepreneurship) compared with other subjects, the difference lies in the content of courses and learning models. This is because the atmosphere campus academic and business nuances. The application of the model of entrepreneurial learning is done through a contextual approach or CTL make students actively in learning. The results of the application of entrepreneurship with contextual learning can be seen from the students' creative entrepreneurship, business and product appearance tangible manifestation and proven to generate revenue. The most prominent constraint is a mindset change, that is change the mindset pass to an employee (work) to pass into entrepreneurs (have my own business)